Entre deux, entre trois… - Abdellatif Fdil (Lengas)
Morocco is a country where cultural and linguistic diversity is a founding principle registered in the constitution and that all rules set out in any level must respect. The purpose of this study is precisely to show that an approach of the preservation of linguistic diversity in the Moroccan cinema  or in the entire Mediterranean sea, is not moderated to achieve the desired result. Such a problem generated when the pressures of expansionist and radical ideologies on small languages are outside of the report creation and film reception. Moreover, since 2000, the representation of the linguistic identity in the Moroccan microcosm continues to become an integral part of the socio-cultural composition, artistic, literary and cinematic.